Manifesting the Future - Shaffeeullah, Nikki; Arlow, Nevada; Boulay, Jenn; Sarker, Senjuti (Theatre Research in Canada / Recherches théâtrales au Canada)

(untitled) (University of Toronto Press, 2020)
This series of first-person reflections by emerging artists meditates on the future of theatre and performance. Written collectively by a past artistic director and recent participants of the AMY (Artist Mentoring Youth) Project, a Toronto-based arts organization providing free and accessible mentorship and creative opportunities to youth, the article offers specific visions from each contributor: how marginalized artists will disrupt systems of oppression to become part of the mainstream; that any possible future will need to draw from our past, pre-capitalism relationships to performance; and how community-centred approaches to performance will enable the professional sector to become meaningfully equitable.